N-Arylation of amines, amides, imides and sulfonamides with arylboroxines catalyzed by simple copper salt/EtOH system - Zhang-Guo Zheng; Jun Wen; Na Wang; Bo Wu; Xiao-Qi Yu (Beilstein Journal of Organic Chemistry, 2008)
The coupling of arylboroxines with a variety of amines, amides, imides and sulfonamides catalyzed by a copper salt/EtOH system has been developed. In the absence of a base or additive the corresponding N-arylation products were obtained in moderate to excellent yields.